Internal migration, living close to family, and individual labour market outcomes in Spain - Clara Helena Mulder; Isabel Palomares-Linares; Sergi Vidal (Comparative Population Studies (CPoS), 2022)
Migration is often viewed as a way to enhance occupational careers. However, particularly in Mediterranean countries, labour market outcomes may also depend on local family resources. We investigate how men's and women's labour market outcomes differ between (1) those who migrated and those who did not; and (2) those who live close to family and those who live farther away. Our main contributions are the investigation of the association between migration and labour market outcomes in a different context than the more commonly studied Northern and Western European countries and the United States, and of the role of living close to family in labour market outcomes. We used a sample of labour market participants from the "Attitudes and Expectations About Mobility" survey, conducted in Spain in 2019. Our results show that the likelihood of being a professional is greater for women who migrated than for those who did not, and that the likelihood of being unemployed or in a temporary job is lower for women who live close to family than for those who do not, but neither association was found for men. The finding for living close to family is in line with the notion that nearby family may protect women in particular from precarious labour market positions. The finding for migration differs from previous findings for Northern and Western Europe and the United States, which indicate that migration is beneficial to men in particular. This difference might be specific to a low-migration context, but data limitations prevent firm conclusions.
urn:nbn:de:bib-cpos-2022-01en2
Keywords: 300; Distance to family; Family relationships; Migration; Socio-economic status; Spain; Unemployment